The Internalization of Externalities in The Production of Electricity: Willingness to Pay for the Attributes of a Policy for Renewable Energy - Alberto Longo; Anil Markandya; Marta Petrucci (Fondazione Eni Enrico Mattei (FEEM), 2006)
This paper investigates the willingness to pay of a sample of residents of Bath, England, for a hypothetical program that promotes the production of renewable energy. Using choice experiments, we assess the preferences of respondents for a policy for the promotion of renewable energy that (i) contributes to the internalization of the external costs caused by fossil fuel technologies; (ii) affects the security of energy supply; (iii) has an impact on the employment in the energy sector; (iv) and leads to an increase in the electricity bill. Responses to the choice questions show that our respondents are in favour of a policy for renewable energy and that they attach a high value to a policy that brings private and public benefits in terms of climate change and energy security benefits. Our results therefore suggest that consumers are willing to pay a higher price for electricity in order to internalize the external costs in terms of energy security, climate change and air pollution caused by the production of electricity.
Keywords: Q42; Q48; Q51; 330; Non Market Valuation; Choice Experiments; Willingness to Pay; Renewable Energy; Energy Security; Greenhouse Gases Emissions